Robust Guaranteed Cost Switched Controller Design using Static Output Feedback - Bocca, Lucas Favi [UNESP]; Ramos, Igor Thiago Minari [UNESP]; Alves, Uiliam Nelson Lendzion Tomaz; Bizarro, Douglas Buytendorp; Assunção, Edvaldo [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP] (My University, 2022)
In this work, a robust switched controller design using output feedback is proposed. The minimization of the output energy is taken into account as a design strategy to reduce the settling time and oscillations of the closed-loop system output. In the design of the controllers, physical limits of the system outputs are also covered, which is done by considering a convex set of initial conditions. Sufficient LMI conditions to solve the control design are presented in the form of theorems that require the choice of constant parameters. The search for the most adequate parameters was accomplished via the differential evolution algorithm. Moreover, the proposed switched controller design is compared with a constant output feedback gain controller and other methodologies proposed in the literature. Theoretical analyses, two numerical examples and a practical implementation in an active suspension system were carried out to show the advantages of the proposed methodology.
Keywords: Differential evolution; Guaranteed cost; Linear matrix inequalities; Switched static output feedback